Photoluminescence properties of praseodymium doped cerium oxide nanoparticles - Cabral, A. C.; Cavalcante, L. S.; Deus, R. C.; Longo, Elson [UNESP]; Simões, A. Z.; Moura, F. (Elsevier, 2013)
The structural and photoluminescent properties at room temperature of CeO2 nanoparticles synthesized by a Microwave-Assisted Hydrothermal Method (MAH) under different praseodymium contents was undertaken. X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM), UV-vis Spectroscopy (UV-vis), Fourier Transform Raman (FT-Raman) and Photoluminescence (PL) measurements were employed. XRD revealed that the nanoparticles are free of secondary phases and crystallize in the cubic structure while FT-Raman revealed a typical scattering mode of fluorite type. The UV/vis absorption spectroscopy suggested the presence of intermediate energy levels in the band gap of structurally ordered powders. The most intense PL emission was obtained for nanoparticles which represent a lower particle size. © 2013 Elsevier Ltd and Techna Group S.r.l.
Keywords: A. Ceramics; B. Chemical syntheses; B. Powder metallurgy; C. X-ray diffraction